Subdirect Sums of SDD1 Matrices - Xiaoyong Chen; Yaqiang Wang (Journal of Mathematics, 2020)
In this paper, the question of when the subdirect sum of SDD1 matrices is in the class of SDD1 matrices is studied. Some sufficient conditions are given. Moreover, these sufficient conditions only depend on the elements of given matrices; thus, they provide some simple criteria for application. Numerical examples are also presented to illustrate the corresponding results.